The IC‐D score for predicting prophylactic cardioverter‐defibrillator implantation following acute myocardial infarction. Issue 6 (24th April 2021) - Clementy, Nicolas; Bensaid, Reda; Bouteau, Jérémie; Fedida, Joël; Kiavue, Yoann; Socie, Pierre; Ackermann, Romain; Goralski, Marc; Fauchier, Laurent; Bernard, Anne; Angoulvant, Denis; Babuty, Dominique
Abstract: Background: A reduced left ventricular ejection fraction (LVEF) ≤35% ≥6 weeks following an acute myocardial infarction (MI) may indicate prophylactic implantation of a cardioverter‐defibrillator (ICD). We sought to find predictors of absence of significant left ventricular (LV) remodeling post‐MI. Methods: All consecutive patients hospitalized for acute MI with an LVEF ≤35% at discharge in our institution from 2010 were retrospectively included. Patients were assigned to two groups according to the persistence of an LVEF ≤35% (ICD+) or a recovery >35% (ICD‐). Logistic regression was performed to build a predictive score, which was then externally validated. Results: Among a total of 1533 consecutive MI patients, 150 met inclusion criteria, 53 (35%) in the ICD+ group and 97 in the ICD group. After multivariable analyses, an LVEF ≤25% at discharge (adjusted OR 6.23 [2.47 to 17.0], p  < .0001) and a CPK peak at the MI acute phase >4600 UI/L (adjusted OR 9.99 [4.27 to 25.3], p  < .0001) both independently predicted non‐recovery at 6 weeks. The IC‐D (Increased Cpk—LV Dysfunction) score predicted persistent LVEF ≤35% with areas under curve of 0.83 and 0.73, in the study population and in a multicenter validation cohort of 150 patients, respectively ( p  < .0001). Conclusions: The association of a severely reduced LVEF and a major release of myocardial necrosis biomarkers at the acute phase of MI predict unfavorable remodeling, and prophylactic ICD implantation.